Speed control for traction motor of urban electrified train in field weakening region based on backstepping method - Thu Anh, An Thi Hoai; Tung, Ngo Manh (Bulletin of Electrical Engineering and Informatics, 2024)
Tractor motors always operate in the speed region higher than rated speed, but is limited to the module of the stator current, stator voltage vectors. Additionally, mathematical model of traction motor has shown nonlinearity through the product of the state variables ???, ??? with the input variable ??:?????, ?????. Therefore, this paper focuses on the study of speed control of traction motors in weakening field region while optimizing torque control, and choosing the backstepping method in designing speed–flux controller in order to solve the nonlinear structure. The simulation results of the responses: speed, torque, power, and flux performed on MATLAB/Simulink software with parameters collected from metro Nhon-Hanoi Station, Vietnam have proven the correctness in theoretical research.